Spectroscopic Studies on the Biomolecular Recognition of Toluidine Blue: Key Information Towards Development of a Non-Contact, Non-Invasive Device for Oral Cancer Detection - Singh, Soumendra; Halder, Animesh; Sinha, Oindrila; Chakrabarty, Nilasha; Chatterjee, Tanima; Adhikari, Aniruddha; Singh, Priya; Shikha, Deep; Ghosh, Ria; Banerjee, Amrita; Das Mahapatra, Partha Pratim; Mandhar, Amit; et al. (Frontiers in Oncology, 2020)
Molecular interaction of aromatic dyes with biological macromolecules are important for the development of minimally invasive disease diagnostic biotechnologies. In the present work, we have used Toluidine Blue (TB) as a model dye, which is a well-known staining agent for the diagnosis of oral cancer and have studied the interaction of various biological macromolecules (protein and DNA) with the dye at different pH. Our spectroscopic studies confirm that TB interacts with Human Serum Albumin (HSA), a model protein at very high pH conditions which is very hard to achieve physiologically. On the other hand, TB significantly interacts with the DNA at physiological pH value (7.4). Our molecular studies strengthen the understanding of the Toluidine Blue staining of cancer cells, where the relative ratio of the nucleic acids is higher than the normal intracellular content. We have also developed a non-invasive, non-contact spectroscopic technique to explore the possibility of quantitatively detecting oral cancer by exploiting the interaction of TB with DNA. We have also reported development of a prototype named “Oral-O-Scope” for the detection of Oral cancer and have carried out human studies using the prototype.